Design of web-based boarding house information system at bunda kosan - Jimmie; Riska Yuniza (International Journal Cister, 2023)
Technology can be said to be very important in today’s life, increasingly advanced technological developments can make it easier for people to carry out daily activities. in a developed area, especially urban areas, of course, there are a lot of immigrants from outside the area to work, school, study, or vacation which of course they need a temporary place to live while carrying out their activities. one of them is to find a boarding house. a boarding house is a home-based business that provides a place or room to rent or live in to tenants who need a place. searching for a boarding house conventionally by asking the community or residents takes a long time to visit the palce and compare it with other options. the purpose of this study is to design and produce systems and information that are precise and time efficient, the method used is obsevation and system development using the waterfall method. the design of a web-based boarding house rental information system can make it easier for users to search and rent without having to come directly to the location so as to save time and costs. can help boarding house owners carry out promotions so that many people know about boarding houses and assist in managing transaction data to make it easier to make payments directly.